Technical and economic feasibility of ethanol production in cashew apple juice from Saccharomyces cerevisiae flocculant - Ãlvaro Daniel Teles Pinheiro (2015)
Given the current situation in which it is the global energy sector, biofuels have been gaining more space, earning special attention the ethanol, which has shown growing demands. From this scenario, the objective of this work was to develop a bioprocess technically and economically practicable for ethanol production from cashew apple juice, using yeast Saccharomyces cerevisiae (CCA008) genetically modified containing a flocculent gene (FLO5α). The work was divided in 4 four stages that are linked throughout the study. In the first stage was evaluated the temperature influence (26, 30, 34, 38 and 42ÂC), the inoculum concentration (3, 5, 8 and 10 g.L-1) and the stirring speed (80, 150, 300, 490, 650 and 800 rpm), so it could be determined the best conditions to maximize ethanol production. It was observed that the temperature operating parameter, the initial cellular concentration, substrate concentration and stirring exerted influence on the alcoholic fermentation of the cashew apple juice. The best performance to the fermentative process (98,8 %) happened when the process was conducted at 34 ÂC, under 150 rpm stirring and 5 g.L-1 of initially cell concentration. The second stage was intended to describe the process efficiency in face of the operation parameters evaluated in fermentation. To this end, it was successfully used statistic models to describe the interaction between the initial substrate concentration, temperature, initial cell concentration, stirring and their possible effects on the yield. The model that best fit the experimental data was used to obtain the optimum conditions from the operating variables, indicating the following conditions as great: substrate concentration (S0) of 102 g.L-1, temperature (T) at 34ÂC, inoculum concentration (X0) of 5 g.L-1 and stirring (Agit) of 140 rpm, predicting a 98,80 % of efficiency. In the third stage was studied ethanol production in optimum conditions, being used to implement the scale up process, in which the data obtained in a 1L bioreactor batch were used to predict the fermentation behavior in a 14L bioreactor batch, using the volumetric power consumption as a parameter to scale-up. Using this factor as being of 10,67 kW/m3, it was possible to calculate the fermenter stirring power in a 14 times bigger volume, as well as foresee which stirring would be necessary so the fermentation can occur, similarly as in the lower volume fermenter. Results showed that yield from the 14L bioreactor were satisfactory, having a small difference (96,56 % Â 0,3 %) between yield from the 1L bioreactor (98,80 % Â 1,6 %). The fourth and last stage was rated the technical and economic viability of the process. Analyzing results, it is possible to say the industrial process here proponed has shown technical viability, since the value obtained for the process yield (68 L/ton), was close to sugar cane fermentation (61 â 72 L/ton). However, it did not show economic viability since the industrial unity provides negative cash flow (- R$ 93.840.874) in the end of 10 years that was analyzed. So, new studies must be conducted in order to make this process economically viable, this possibility being observed in various scenarios generated in analyzing the sensibility of process, which presents possible economically viable settings.